Theoretical and practical aspects of the evaluation of health-related quality of life (HRQOL) - Zaręba, Monika; Zaręba, Anita; Jopkiewicz, Andrzej; M. Jopkiewicz, Agata (Medical Studies/Studia Medyczne, 2021)
The aim of this paper is to present various theoretical and practical aspects of health-related quality of life (HRQOL). Clinical studies show that, along with the classic quantitative indicators of treatment success regarding the patient’s life expectancy, the parameters of quality of life, which include, among others, a reduced number of symptoms of disease, improved well-being and mood, as well as physical fitness, are of great importance. The interest in the problem of quality of life is also conducive to the development of new research tools. However, it should be remembered that regardless of the tool used, the quality of life felt by the patient is individual and changes over time. The ease of use of questionnaires and analogue scales allows us to obtain various types of information, provided that certain criteria are met.